Is root exposure a good marker of periodontal disease? (Bulletin of the International Association for Paleodontology, 2021)
In bioarchaeological studies dental root exposure is often used as a marker of periodontal disease; these studies are based on classical methods assuming alveolar resorption as the only (or the main) cause of root exposure. However, several papers suggested that root exposure depends not only on alveolar resorption, but also on other mechanisms. Continuous eruption and compensatory eruption might also cause root exposure in absence of periodontal disease. We investigated this topic on a skeletal sample from the medieval cemetery of Pieve di San Pancrazio in Sestino (Arezzo, Italy). We collected data on root exposure, dental wear and alveolar bone status on permanent mandibular teeth of individuals from juvenile to senile and tested the relationship among these features. The results show that root exposure strongly correlates with dental wear, also in absence of morphological markers of periodontal disease. In our sample, the use of root exposure as a marker of periodontal disease led to a mis-diagnosis in 10% to 50% of the teeth. We encourage the use of methods based on alveolar bone morphology, which allows discriminating periodontal disease independently of root exposure.